2014
DOI: 10.1371/journal.pone.0111139
|View full text |Cite|
|
Sign up to set email alerts
|

Bioimpedance Spectroscopy for Assessment of Volume Status in Patients before and after General Anaesthesia

Abstract: BackgroundTechnically assisted assessment of volume status before surgery may be useful to direct intraoperative fluid administration. We therefore tested a recently developed whole-body bioimpedance spectroscopy device to determine pre- to postoperative fluid distribution.MethodsUsing a three-compartment physiologic tissue model, the body composition monitor (BCM, Fresenius Medical Care, Germany) measures total body fluid volume, extracellular volume, intracellular volume and fluid overload as surplus or defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 43 publications
5
29
0
Order By: Relevance
“…Liberal crystalloid infusion also increased ECW by more than restrictive infusion. An increase in ECW following intraoperative fluid infusion has also been observed by Ernstbrunner et al 5 They observed a strong correlation between the net perioperative fluid balance and a change in ECW in patients undergoing elective gynecological surgery under general anesthesia. This increase in ECW corresponded to TBW, but the authors proposed net perioperative fluid balance and postoperative capillary leak index as significant individual predictors for changes in ECW.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Liberal crystalloid infusion also increased ECW by more than restrictive infusion. An increase in ECW following intraoperative fluid infusion has also been observed by Ernstbrunner et al 5 They observed a strong correlation between the net perioperative fluid balance and a change in ECW in patients undergoing elective gynecological surgery under general anesthesia. This increase in ECW corresponded to TBW, but the authors proposed net perioperative fluid balance and postoperative capillary leak index as significant individual predictors for changes in ECW.…”
Section: Discussionsupporting
confidence: 67%
“…30 Other authors have proposed BIA as a sensitive and easy method for measuring perioperative fluid administration in patients undergoing elective surgery. 5 We have also documented the usefulness of BIA in perioperative clinical practice, though we placed the electrodes on the body side opposite to the surgery. Surgery-related tissue edema and wound hematoma may have significantly disturbed the final results of BIA measurement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the noninvasive nature of bioimpedance makes it particularly well suited for measuring longitudinal changes. Notably, BIS techniques have recently shown promise in assessing body composition and mortality risk in people on dialysis 81 and in managing fluid status in dialysis 88 93 as well as surgery 92 and critically illness 91 …”
Section: Bioimpedancementioning
confidence: 99%
“…The cut-off BIA values used for defining normal-, over-and dehydrated patients were as for patients undergoing chronic dialysis. These values have also been used by other authors with regard to perioperative patient assessment [39]. The mean postoperative TBW and ECW increased significantly, and so did the ECW/ICW ratio from preoperative 0.85 to postoperative 0.93.…”
Section: Discussionmentioning
confidence: 92%